Osoba prezbitera w nauczaniu Jana Pawła II na podstawie jego homilii wygłoszonych podczas święceń prezbiteratu - Prajsnar, Joanna (Studia Pastoralne, 2007)
<span class="citation-1370 citation-1371 citation-1372 citation-1373 citation-1374 citation-1375 citation-1376 citation-1377 citation-1378 citation-1379 citation-1380 citation-1381 citation-1382 citation-1383 citation-1384 citation-1385 citation-end-1385">The article presents the analysis of the contents of John Paul II’s homilies which relate to the issues concerning the identity of the presbyter. <span class="citation-1354 citation-1355 citation-1356 citation-1357 citation-1358 citation-1359 citation-1360 citation-1361 citation-1362 citation-1363 citation-1364 citation-1365 citation-1366 citation-1367 citation-1368 citation-1369 citation-end-1369">Following the Pope’s thought one can notice the emphasis of the fact tha<span class="citation-1354 citation-1355 citation-1356 citation-1357 citation-1358 citation-1359 citation-1360 citation-1361 citation-1362 citation-1363 citation-1364 citation-1365 citation-1366 citation-1367 citation-1368 citation-end-1368">t the presbyter participates in the mission of C<span class="citation-1354 citation-1355 citation-1356 citation-1357 citation-1358 citation-1359 citation-1360 citation-1361 citation-1362 citation-1363 citation-1364 citation-1365 citation-1366 citation-1367 citation-end-1367">hrist Himself. The participation in the mission c<span class="citation-1354 citation-1355 citation-1356 citation-1357 citation-1358 citation-1359 citation-1360 citation-1361 citation-1362 citation-1363 citation-1364 citation-1365 citation-1366 citation-end-1366">onsists in fulfilling His perfect sacrifice, celebrating all the sacraments and preaching the Gospel. The presbyter holds the ministry in the person of Christ – in persona Christi – meaning it is done by God Himself. This participation in Christ’s mission is guaranteed by the laying on of hands, in which way the first disciples of the Master appointed their helpers and successors. Thus, the identity of the presbyter is shaped by a strong bond with God and His salvation. To fulfill the salvation the presbyter must efface himself and let Jesus be the master of his gestures, words and deeds. Life in such a close relationship with Christ is a great mystery of God’s plan who entrusts Himself to weak and sinful people. Such reality is a great gift for anyone who, thanks to the works of the priest, can directly experience intimacy with God and His saving acts. It is also a gift for the presbyter himself who, despite his fragility, is blessed with a special friendship with Jesus Christ. The one chosen to priesthood is marked with a lasting seal of priestly ordination meaning that he becomes God’s beloved servant forever, regardless of his current spiritual condition. Such a lifelong honor and commitment may at the same time fill the presbyter with fear because of his own littleness and imperfection. Nevertheless, the presbyter, trusting the efficacy of the words from the ordination ritual „And I am confident of this, that the one who began a good work among you will bring it to completion by the day of Jesus Christ” (cf. Phlp 1,6) can fulfill the ministry, devoting himself to Christ with trust.